A model rural rehabilitation service station in China- Evaluation after 5 years - HL Qin; JG Ma; SW Chen; CP Li; Ping-Chung Leung (Archives of Community Medicine and Public Health - Peertechz Publications, 2023)
A simple setup for rehabilitation training was established in 2007 in a rural area of Shanxi Province, China. It made use of an underused facility created for elderly people's leisure time. Simple equipment for rehabilitation training was provided free for the users, and instructions were given by rehab experts, Traditional medical doctors, and social workers. This rural Service Station must be the first of its kind in rural China and deserves scrutinizes for its unique nature. After 5 years of service, a service evaluation of its service nature, service providers, users, and special orientations was completed. It is hoped that this Service Station could be taken as a model of similar rural development in China.